Materials with ferro-antiferroelectric phase transition intented for energy accumulated and converting devices - Ishchuk, V.M.; Spiridonov, N.A. (Functional Materials, 2004)
Considered are the results of development of materials for energy accumulating and converting devices. Requirements to such materials are formulated. Investigated is one of the directions for raising their efficiency which implies increase of electric strength.